(untitled) (Research, Society and Development, 2022)
Objective: To highlight in the literature the role of nurses during the period of pandemic by covid-19 in Primary Care. Methodology: This is an integrative review of a descriptive nature with a qualitative approach; the databases used were MEDLINE, BDENF and LILACS, using the descriptors: "SARS-COV-2", "Coronavirus", "Nursing" and "Primary Care", seeking to answer the following question: "What is the role of nurses in Primary Care during the covid-19 pandemic?”, 14 articles were selected, published between 2019 and 2021. Results: Nursing has reinvented itself to ensure its performance with excellence, both in its role in education and health promotion, as well as in the prevention of diseases and injuries, in order to provide new care in relation to covid-19, continuing the actions of Primary Care. Conclusion: Nursing, during the health crisis, has shown its importance in the health system and its commitment with the lives of individuals, families, communities and groups that they take care of together with the health teams. Therefore, it is necessary for nurses to be able to reinvent themselves in their processes of service to the public, even facing the difficulties several challenges that the health system had already been presenting and that with the advent of the pandemic were enhanced.